Characterization of in vitro metabolites of TM‐2, a potential antitumor drug, in rat, dog and human liver microsomes using liquid chromatography/tandem mass spectrometry. (30th October 2014) - Men, Lei; Zhao, Yunli; Lin, Hongli; Yang, Mingjing; Liu, Hui; Tang, Xing; Yu, Zhiguo
<x xml:space="preserve">Abstract</x> RATIONALE TM‐2 (13‐(N‐Boc‐3‐i‐butylisoserinoyl‐4, 10‐β‐diacetoxy‐2‐α‐benzoyloxy‐5‐β, 20‐epoxy‐1, 13‐α‐dihydroxy‐9‐oxo‐19‐norcyclopropa[g]tax‐11‐ene) is a novel semi‐synthetic taxane derivative. Our previous study demonstrated that it is a promising taxane derivative. The in vitro comparative metabolic profile of a drug between animals and humans is a key issue that should be investigated at early stages of drug development to better select drug candidates. In this study, the in vitro metabolic pathways of TM‐2 in rat, dog and human liver microsomes were established and compared. METHODS TM‐2 was incubated with liver microsomes in the presence of NADPH. Two different types of mass spectrometers – a hybrid linear trap quadrupole orbitrap (LC/LTQ‐Orbitrap) mass spectrometer and a triple‐quadrupole tandem mass spectrometer (LC/QqQ) were employed to acquire structural information of TM‐2 metabolites. Accurate mass measurement using LC/LTQ‐Orbitrap was used to determine the accurate mass data and elemental compositions of metabolites thereby confirming the proposed structures of the metabolites. For the chemical inhibition study, selective P450 inhibitors were added to incubations to initially characterize the cytochrome P450 (CYP) enzymes involved in the metabolism of TM‐2. RESULTS A total of 12 components (M1–M12) were detected and identified as the metabolites of TM‐2 in vitro. M1–M5 were formed by hydroxylation of the taxane ring or the lateral chain. Hydroxylated products can be further oxidized to the dihydroxylated metabolites M6–M10. M11 was a trihydroxylated metabolite. M12 was tentatively identified as a carboxylic acid derivative. The metabolism of TM‐2 is much the same in all three species with some differences. The chemical inhibition study initially demonstrated that the formation of M2, the major metabolite of TM‐2, is mainly mediated by CYP3A4. CONCLUSIONS Hydroxylation is the major biotransformation of the TM‐2 pathway in vitro. CYP3A4 may play a dominant role in the formation of M2 in liver microsomes. The knowledge of the metabolic pathways of TM‐2 is important to support further research of TM‐2. Copyright © 2014 John Wiley & Sons, Ltd.